Simplify. mn^-4/p^0 q^-2
a) mq^2/n^4
b) mp/n^4
c)mn^-4q^2p^0
d)q^2/mm^4 ****
****= my answer.
Please check this for me!
3 answers
d is the right answer
Thank you! @seba :D
mn^-4 / (p^0 q^-2)
= (m/n^4)/(1/q^2)
= mq^2/n^4
(mn^-4/p^0) q^-2
= (m/n^4) * 1/q^2
= m/(n^4 q^2)
what you wrote was ambiguous.
But in no case is there an m in the denominator.
= (m/n^4)/(1/q^2)
= mq^2/n^4
(mn^-4/p^0) q^-2
= (m/n^4) * 1/q^2
= m/(n^4 q^2)
what you wrote was ambiguous.
But in no case is there an m in the denominator.